Environmental impact assessment of strawberry cultivation : the case of Cyprus - Kokkini, Anna (My University, 2025)
Strawberry cultivation possesses a significant role in Cyprus agricultural sector, yet its environmental impact remains a critical concern. This study employs a Life Cycle Assessment (LCA) methodology to evaluate the environmental burdens associated with three distinct strawberry production systems: (1) open-field cultivation in soil, (2) unheated high tunnel cultivation in soil and, (3) unheated high tunnel soilless (peat moss) cultivation. To identify the most relevant cultivation systems for analysis, we designed and distributed questionnaires to local farmers. Based on the responses received, we focused our study on these prevalent cultivation methods. The analysis conducted encompassed key impact categories, including global warming potential, terrestrial acidification, freshwater eutrophication, terrestrial ecotoxicity, human toxicity, and land use and water consumption. The findings indicated that the peat moss based soilless system exhibited the highest environmental burden, primarily due to the extensive use of inorganic fertilizers and fossil fuel consumption. Conversely, unheated high tunnel cultivation in soil emerged as the most environmentally sustainable method, demonstrating lower emissions and reduced consumption. Open- field systems, while widely practiced, they present significant challenges concerning water use efficiency and soil degradation. This research underscores the eminent need for sustainable agricultural practices tailored to Cyprus unique climatic and resource constraints. By optimizing irrigation strategies, minimizing synthetic input dependency and promoting resource-efficient cultivation methods, the environmental footprint of strawberry production can be significantly reduced. The insights from this study are expected to contribute to the development of best practices for eco-friendly strawberry cultivation.
Keywords: Fragaria x ananassa; life cycle assessment; irrigation; sustainability; global warming potential; terrestrial acidification; freshwater eutrophication; terrestrial ecotoxicity; human toxicity; land use